Setting priority conservation management regions to reverse rapid range decline of a key neotropical forest ungulate - Luca Borger (Global Ecology and Conservation, 2021)
Mammals are important components of biodiversity that have been drastically and rapidly impacted by climate change, habitat loss, and anthropogenic pressure. Understanding key species distribution to optimize conservation targets is both urgent and necessary to reverse the current biodiversity crisis. Herein, we applied habitat suitability models for a key Neotropical forest ungulate, the white-lipped peccary (WLP Tayassu pecari), to investigate the effects of climate and landscape modifications on its distribution, which has been drastically reduced in Brazil. We used 318 primary records of WLP to derive habitat suitability maps across Brazil. Our models included bioclimatic, topographic, landscape, and human influence predictors in two modelling approaches. Models including all categories of predictors obtained the highest predictive ability and showed prevalence of suitable areas in forested regions of the country, covering 49% of the Brazilian territory. Filtering out small forest fragments (<2050 ha) reduced the suitable area by 5%, with a further reduction of 4% that was caused by deforestation until 2020, therefore until 2020, the species has suffered a reduction of ~60% from its historical range in Brazil. Of the 40% of the Brazilian territory suitable to WLP, only 12% are protected. In the Atlantic Forest, only half of all protected areas have suitable habitat for WLP and even less in Pantanal (44%), Cerrado (14%) and Caatinga (7%). In a second modelling approach, mapping the areas with suitable climate and those with suitable landscapes separately, allowed us to identify four categories of conservation values, and showed that only 17% of the Brazilian territory has both high landscape and climatic suitability for WLP. Our models can help with complementary conservation management strategies and actions that could be essential in slowing down and possibly reversing current trends of population and geographic range reductions for te species, thereby averting a possible future collapse of forest ecosystem functioning in the Neotropical region.